The School Interference Questionnaire: Examining a Novel Measure of Mental Health–Related Academic Functional Impairment in Youth. (September 2022) - Zendegui, Elaina A.; Bennett, Shannon M.; Desai, Payal; Schild, Jennifer S.; Beaumont, Renae B.; Chiu, Angela W. M.
This article reports on the development and initial psychometric properties of the School Interference Questionnaire (SIQ), a questionnaire designed to assess both academic functional impairment related to mental health problems and the type and frequency of school refusal behavior. Participants were 110 youth ages 13 to 18 years ( M = 15.41 years, SD = 1.42) admitted to an adolescent partial hospitalization program. The majority of participants identified as female (57.3%), Caucasian (59.1%), and non-Latino (70.0%). Internal consistency of the 12 SIQ core interference items was excellent (Cronbach's α = .91). The factor structure suggested that a single factor was appropriate for the 12 school interference items. Correlations between the SIQ and other measures in this study provided support for construct validity. The average SIQ core interference item score showed evidence of convergent validity via correlations with measures of school refusal, global disability, and internalizing symptoms. The SIQ also exhibited no significant association with timing of study enrollment, suggesting evidence for divergent validity. Results provide initial evidence supporting the psychometric properties of this novel measure.